Needs Analysis for Developing Ciputrawangi Agrotourism in Sumedang Regency: An Integration of SWOT Analysis, AHP, and Linear Regression - Nataliningsih Nataliningsih; Gijanto Purbo Suseno; Gumoyo Mumpuni Ningsih; Ilham Nukmanul H (Dinasti International Journal of Education Management and Social Science, 2026)
This research examines the development requirements of Ciputrawangi Agrotourism in Sumedang Regency using SWOT, AHP, and linear regression to formulate sustainable strategies. The site boasts natural attractions like scenic waterfalls, gardens, and convenient access, bolstered by internal strengths such as parking spaces and basic amenities, alongside external opportunities from community backing and rising regional income. Data from seven respondents (village head, managers, traders, and visitors) yielded IFE scores of 3.04 and EFE scores of 2.98, positioning it in Quadrant I (aggressive growth strategy). AHP prioritized six strategies: enhancing facilities, boosting promotion, and environmental conservation. Linear regression indicates that strengths and opportunities significantly mitigate threats (R² = 0.78), affirming the viability of Ciputrawangi Agrotourism.